A unique phenotype in a patient with a rare triplication of the 22q11.2 region and new clinical insights of the 22q11.2 microduplication syndrome: a report of two cases - Vaz, Sara O. (2015)
Background: The rearrangements of the 22q11.2 chromosomal region, most frequently deletions and duplications, have been known to be responsible for multiple congenital anomaly disorders. These rearrangements are implicated in syndromes that have some phenotypic resemblances. While the 22q11.2 deletion, also known as DiGeorge/Velocardiofacial syndrome, has common features that include cardiac abnormalities, thymic hypoplasia, characteristic face, hypocalcemia, cognitive delay, palatal defects, velopharyngeal insufficiency, and other malformations, the microduplication syndrome is largely undetected. This is mainly because phenotypic appearance is variable, milder, less characteristic and unpredictable. In this paper, we report the clinical evaluation and followup of two patients affected by 22q11.2 rearrangements, emphasizing new phenotypic features associated with duplication and triplication of this genomic region. Case Presentation: Patient 1 is a 24 year-old female with 22q11.2 duplication who has a heart defect (ostium secundum atrial septal defect) and supernumerary teeth (hyperdontia), a feature previously not reported in patients with 22q11.2 microduplication syndrome. Her monozygotic twin sister, who died at the age of one month, had a different heart defect (truncus arteriousus). Patient 2 is a 20 year-old female with a 22q11.2 triplication who had a father with 22q11.2 duplication. In comparison to the first case reported in the literature, she has an aggravated phenotype characterized by heart defects (restrictive VSD and membranous subaortic stenosis), and presented other facial dysmorphisms and urogenital malformations (ovarian cyst). Additionally, she has a hemangioma planum on the right side of her face, a feature of Sturge-Weber syndrome. Conclusions: In this report, we described hyperdontia as a new feature of 22q11.2 microdeletion syndrome. Moreover, this syndrome was diagnosed in a patient who had a deceased monozygotic twin affected with a different heart defect, which corresponds to a phenotypic discordance never reported in the literature. Case 2 is the second clinical report of 22q11.2 triplication and presents an aggravated phenotype in contrast to the patient previously reported.